"Today I Had an Eye Appointment, and I’m Still Blind": Crip Humor, Storytelling, and Narrative Positioning of the Disabled Self - Milbrodt, Teresa (Disability Studies Quarterly, 2018)
While able-bodied people may perceive the lives of disabled individuals as "tragic," disabled people often do not believe that to be the case. This paper argues that one way this incongruity might be mediated is through the use of humor and storytelling to create a space of understanding and portray disabled people as having independence and agency. The paper analyzes humorous stories told by disabled individuals in a variety of social situations, interacting both with able-bodied and disabled communities. While disabled people are often positioned by society as helpless, spiteful, and/or lacking agency and control, by telling comic stories, individuals can position themselves on their own terms, and subvert dominant ideologies.